Laser performance of in-band pumped Er : LiYF4 and Er : LiLuF4 crystals. (February 2016) - Gorbachenya, K.N.; Kurilchik, S.V.; Kisel, V.E.; Yasukevich, A.S.; Kuleshov, N.V.; Nizamutdinov, A.S.; Korableva, S.L.; Semashko, V.V.
Abstract: Spectroscopic properties of and crystals in the spectral region near and the lasing characteristics of these crystals under in-band pumping at a wavelength of are studied. With the crystal, the maximum slope efficiency with respect to the absorbed pump power was 44 % at a wavelength of . Continuous-wave operation of an in-band pumped laser is obtained for the first time. The output power at a wavelength of was with a slope efficiency of 21%.